Medical Specimen Incubator Model 2022-2023 - Hamza, Mohammed Baqir Sattar; Mahdi, Ali Rasheed; Abdullah, Dr. Awfa Abdulrasool; Hasan, Dahlia Mohammed Ali (American Journal of Bioscience and Clinical Integrity, 2024)
The laboratory incubator is considered one of the very important devices in the health aspect. It is necessary for experimental work in the biology of microorganisms and provides an ideal medium suitable for the growth and reproduction of various types of microorganisms. Such as bacteria that infect the human body, causing diseases. In some diseases, it is difficult when examining a blood sample or any other fluids of a person’s body, once it determines the type of infectious bacteria that causes the disease due to its incomplete growth or lack of density within the sample. In this case the doctor resorts to making a culture of these bacteria to obtain a large number of them, and thus we are able to know the type of bacteria, and accordingly, it is possible to determine its type accurately, and even determine the type of antibiotic suitable for successful treatment with it. The laboratory incubator is relatively expensive. In this project, we worked on providing an ultraviolet sterilization system for the incubator by using low-priced materials. We also provided the incubator with a room that has a temperature system and its own control panel, where it is possible to place more than one sample and more than one type inside the incubator itself. Thus, we exploited the space and time and the cost of making two incubators instead of one incubator. We got very good results compared to other traditional incubators that have one system, the lowest possible cost and the available capabilities.